Quality of life of Bangladesh migrant construction workers in Malaysia - Haque, Md Wahidul
Millions of migrant labours are working in Malaysia from neighbouring countries, including Bangladesh. It is evident from many researches that Bangladeshi workers mostly migrate to Malaysia as unskilled labours. Yet, there is less research on the Quality of Life (QoL) of Bangladeshi migrant construction workers in Malaysia. This study, therefore, aims to explore the indicators and factors affecting their QoL and developing a QoL Model for Bangladeshi migrant construction workers in Malaysia. This study employs mixed-methodology, a combination of qualitative and quantitative research. For qualitative method, an in-depth interview of 30 informants, and observations of 13 construction sites were conducted. The quantitative method used que tionnaire surv y to interview 385 respondents from four states of peninsular Malaysia. The scope of the study covered only the Bangladeshi construction workers who have been working in Malaysia for less than ten years. Thematic analysis by tla ti v a u d for qualitative analysis, and descriptive and inferential statistics were used for quantitative analysis by SPSS and Smart PLS. The finding of Structural Equation Modeling (SEM) indicates that the exogenous constructs predict 47% of the endogenous construct (R2 = 0.470). Results show that most of the workers staying for less than eight years are leading a low and medium QoL. The result also shows that the second order constructs namely income, expenses, saving, ownership, health and housing are the main indicators of the workers' QoL. The result also indicates a significant relationship of the factors, namely support, job, religion and communit with QoL. The result further indicated that religion contributes most significantly towards QoL. On the contrary, education and training, and security and fi eedom are not significant to Bangladeshi workers' QoL. In line with the quantitative results, the thematic analysis indicated that overemphasise on economic activities and misconceptions regarding security and freedom are leading the workers towards a low QoL. This study is able to establish a QoL model named as "Butterfly Model" for Bangladeshi construction workers in Malaysia. Results can be used to improve the QoL of Bangladeshi workers, along with the economic benefit of both Malaysia and Bangladesh.